Digitalisasi Arsip Kantor Kementrian Agama Sidoarjo Menggunakan Aplikasi Srikandi Ver. 3 - Dzulhilmi, Muhammad Aziz; Mustofa, Ali; Fauzi, Ahmad; Lubab, Ahmad (Jurnal Kependidikan Islam, 2025)
Archival digitization constitutes a strategic initiative for enhancing efficient and contemporary document management, particularly within governmental bodies. This research analyzes the deployment of the SRIKANDI (Integrated Dynamic Archival Information System) version 3 application at the Sidoarjo Ministry of Religious Affairs Office to advance its archival digitization agenda. As a technological innovation, SRIKANDI is engineered to expedite archival management transformation, encompassing documentation, tracking, and data security. Utilizing a descriptive qualitative methodology, data was gathered via observation, in-depth interviews, and document analysis. Findings reveal that the application substantially augments management effectiveness through superior data accessibility, diminished document loss risks, and heightened time efficiency. Nonetheless, implementation challenges, including the necessity for comprehensive user training and robust technological infrastructure, were observed. The study concludes that SRIKANDI version 3 is a pertinent solution for supporting digitization, contingent upon the provision of continuous user assistance and capacity-building initiatives. Recommendations entail developing more intuitive application features and intensifying technical training programs for personnel.